2010
DOI: 10.4049/jimmunol.1000238
|View full text |Cite
|
Sign up to set email alerts
|

Applying TLR Synergy in Immunotherapy: Implications in Cutaneous Leishmaniasis

Abstract: Therapy of intracellular pathogens can be complicated by drug toxicity, drug resistance and the need for prolonged treatment regimens. One approach which has shown promise is immunotherapy. Leishmaniasis, a vector-borne disease ranked among the six most important tropical infectious diseases by the WHO, has been treated clinically with crude or defined vaccine preparations or cytokines such as IFN-γ and GM-CSF in combination with chemotherapy. We have attempted to develop an improved and defined immunotherapeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
66
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 59 publications
(99 reference statements)
3
66
0
Order By: Relevance
“…The contrasting effects of TLR2 and TLR4 signaling implied that engaging TLR2 would promote infection, while blockading TLR2 or triggering TLR4 would strengthen resistance and produce antileishmanial activity. These assumptions were tested in WT mice with established infection by injecting Pam3CSK4 (27,(52)(53)(54), anti-TLR2 MAb (36,37), or GLA-SE, a TLR4 agonist (33).…”
Section: Effect Of Il-10r Blockade In Tlr2mentioning
confidence: 99%
“…The contrasting effects of TLR2 and TLR4 signaling implied that engaging TLR2 would promote infection, while blockading TLR2 or triggering TLR4 would strengthen resistance and produce antileishmanial activity. These assumptions were tested in WT mice with established infection by injecting Pam3CSK4 (27,(52)(53)(54), anti-TLR2 MAb (36,37), or GLA-SE, a TLR4 agonist (33).…”
Section: Effect Of Il-10r Blockade In Tlr2mentioning
confidence: 99%
“…Raman et al have demosntrated that achieving strong and effective T cell responses against cutaneous leishmaniasis in mice required the combination of MPLA and CpG along with the antigen. However, the administration of the antigen with each adjuvant separately did not produce an optimal response [80]. In the same way, Zhu et al found that mice immune response upon vaccination against HIV using envelope peptide along with macrophage-activating lipoprotein 2 (MALP2, TLR2/6), poly(I:C), CpG was importantly improved [81].…”
Section: In Vivo Targeting Of Antigens and Adjuvant-activation Of Denmentioning
confidence: 81%
“…Previous studies have utilized CpG alone (15) or in combination with other adjuvants or L. major antigen for both treatment and prevention of experimental leishmaniasis (68). However, therapeutic treatment by CpG alone of L. major is controversial, and both healing and the absence of an effect have been reported (14,15); where healing was observed, however, this was accompanied by a Th1 response. In the current study, we employed a high dose of CpG, administered locally after the development of lesions, which induces a regulatory response and effectively ameliorates L. (V.) panamensis infection.…”
Section: Discussionmentioning
confidence: 91%
“…Generally, treatment of leishmaniasis (vaccine immunotherapy or adjuvant alone) with CpG or other TLR ligands directed the host immune response toward Th1-like (higher levels of IFN-␥) or multifunctional T cell responses, which were associated with healing (14,24,26,27). However, ligation of TLRs can activate or downregulate the immune response; studies indicate that the precise effect can be dose dependent.…”
mentioning
confidence: 99%
See 1 more Smart Citation